Implementation of Learning Management System in Information Technologi Education UNISRI Surakarta - Tigus Juni Betri (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The solutions in current learning system is Electronic Learning or well known withE-Learning. Implementation of Electronic-Based Learning can be more varied andat the same time can eliminate the saturation of learners. In Education perception,aplication for E-Learning usually called with Learning Management System(LMS). This software includes material, quizzes , courses learning method and allof them are summarized in one application. Implementation of LMS in Universityof Slamet Riyadi Surakarta not running maximally. The solution for the problem isbetter to design LMS and it must be implemented for student. The new appliactionof LMS had been created and can be implemented for the students as end user.Thesubject of this research is the students who are taking class in InformationTechnology Education. They will take some courses with this electronic learningmethod that can be opened by online Meanwhile questioneer and testing areapplied to gain the data. The questioneer were done toward students after they aretaking courses with the application. Testing was conducted directly in learningprocess after they are given questioneer to be fullfilled. The data that collected thenanalyzed using experimental quantitative research. After the data accuratelycollected, then analyzed using Partial Least Square to measure reception level bythe students as end user.The results showed, based on the questionnaire and testingto end users can be concluded that the application LMS offered can be accepted forthe students. This is shown from the statistical results of the analysis of theinfluence between variables that are formulated. Hypothesis of influence betweenvariables most or dominant produce application acceptableKeywords: Application, E-Learning, End User, Information Technology, LMS